Experimental study of fatigue age on SUP-9 leaf spring steel which received heat treatment and shot peening processes - Achmad, Zainun; Ismail, Al Emran (Penerbit UTHM, 2020)
One aspect of the technical defect of leaf springs that are subjected to dynamic loads is fatigue defects which cause failure, as a result of uneven road surface or impact. Then leaf springs are expected to have a higher fatigue resistance limit. To improve the mechanical properties of leaf spring steel by providing heat treatment and shot peening processes, which will provide compressive residual stress to the surface, thereby improving the fatigue resistance of the spring. In this study, SUP 9 steel specimen has dimensions of 7 mm and a width of 50 mm, the heat treatment process is carried out at an austenitizing temperature of 920⁰C and 480 ⁰C temper temperature, for shot peening it is carried out at a pressure of 5 kg / cm², a shot diameter of 0.8 mm, with a peening time of 15 seconds, 17 seconds and 20 seconds, and testing of tensile, hardness, fatigue, residual stress, and fractography. This study shows that for a long shot time, good results are obtained, namely, the fatigue life has increased 8.7 times from the fatigue life of the spring steel without shot peening with application stress of 217 N / mm², and the residual stress is -847.39 N / mm².